2021
DOI: 10.18332/tpc/134238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin in the abstracts of systematic reviews and meta-analyses of treatments and interventions for smoking cessation

Abstract: INTRODUCTION Smoking cessation treatments and available evidence continue to evolve. To stay current with the latest research, physicians often refer to abstracts of systematic reviews. Because abstracts of systematic reviews may have direct effects on patient care, the information within them should be free of ‘spin’. Spin is a specific way of reporting, intentional or not, to highlight that the beneficial effect of the experimental treatment in terms of efficacy or safety is greater than that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract 33 . However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%) 36 32 …”
Section: Discussionsupporting
confidence: 76%
“…Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract 33 . However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%) 36 32 …”
Section: Discussionsupporting
confidence: 76%
“…Our team's previous investigations found spin in abstracts at rates ranging from 37% in oncology RCTs [18] to 70% in otolaryngology RCTs [37]. More recently, studies have shown that spin frequently occurs in abstracts of systematic reviews [38][39][40][41][42][43][44][45][46][47][48]. As previously mentioned, Ottwell et al [20] identified spin in 31% of the included abstracts of systematic reviews and meta-analyses on acne vulgaris therapies, a finding similar to ours.…”
Section: Xsl • Fosupporting
confidence: 86%
“…After that publication, multiple studies were published on the presence of spin within systematic reviews for different treatment options, including orthopaedics. 7 , 11 , 15 , 18 , 23 , 26 Carr et al 5 published an article in Foot & Ankle Orthopaedics looking at the presence of spin within the systematic reviews of treatment options for Achilles tendon ruptures. The authors identified the presence of spin in 65% of their studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the investigators determined the presence of spin in the abstract of each study. Specifically, the presence of spin was determined after evaluating the full text, based on previously published literature in various aspects of medicine, 7 , 11 , 15 , 18 , 23 , 26 and the type of spin was determined according to the classification by Yavchitz et al 30 Any disagreements between the investigators were resolved by the senior authors (M.V. and M.H.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation